Global Research Trends in Tax Management: A Bibliometric Analysis of Scientific Publications (1990-2025) - Vinhant Gonawan; Rachmat Agus Santoso; F. Fitriana (Manunggal Halim Jaya, 2026)
Tax management has become an increasingly important topic in accounting and taxation research due to growing regulatory complexity, corporate tax efficiency demands, and the expanding role of tax governance. Although the number of publications on tax management has increased substantially, comprehensive evidence regarding the global development of this research field remains limited. This study aims to map global research trends in tax management using a bibliometric approach. Bibliographic data were collected from the Scopus database covering publications from 1990 to 2025. The analysis employed publication trend analysis, cumulative growth analysis, and life cycle analysis to evaluate the evolution and maturity of the research field. The results indicate that tax management research has grown rapidly, particularly after 2015, and has entered the growth stage of its scientific development. The life cycle analysis projects that publication activity will reach its peak around 2032, with a coefficient of determination (R²) of 0.873, indicating a strong model fit. The cumulative growth analysis further suggests considerable opportunities for future research, particularly in emerging areas related to tax governance, digital taxation, and corporate sustainability. This study contributes to the taxation literature by providing a comprehensive overview of the evolution of tax management research and offering valuable insights for researchers and policymakers in identifying future research directions.